2021
DOI: 10.1371/journal.pone.0254087
|View full text |Cite
|
Sign up to set email alerts
|

Online social cohesion reflects real-world group action in Syria during the Arab Spring

Abstract: In recent years, political activists have taken to social media platforms to rapidly reach broad audiences. Despite the prevalence of micro-blogging in these sociopolitical movements, the degree to which virtual mobilization reflects or drives real-world movements is unclear. Here, we explore the dynamics of real-world events and Twitter social cohesion in Syria during the Arab Spring. Using the nonlinear methods cross-recurrence quantification analysis and windowed cross-recurrence quantification analysis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…However, this could be potentially problematic in the case of understanding whether the observed values differ from those values that might be expected simply by chance. We address this concern using approximate permutation tests, which allow a researcher to create and test surrogate time series (i.e., use itself as a baseline; see Chiovaro et al, 2021, andDale, 2017). Permutation tests go beyond the raw frequencies of categories to test the degree to which the structure of the categories across the transcript can be found together more often than would be expected by chance (i.e., the baseline).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, this could be potentially problematic in the case of understanding whether the observed values differ from those values that might be expected simply by chance. We address this concern using approximate permutation tests, which allow a researcher to create and test surrogate time series (i.e., use itself as a baseline; see Chiovaro et al, 2021, andDale, 2017). Permutation tests go beyond the raw frequencies of categories to test the degree to which the structure of the categories across the transcript can be found together more often than would be expected by chance (i.e., the baseline).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, despite its use in various disciplines, it has been scarcely used in analyzing political variables. For example, one study found that online social cohesion during the Arab Spring in Syria was related to the frequency of protests [ 22 ]. For this, they used a variant of RQA, the Cross Recurrence Quantification Analysis, which analyzes the recurrences of two time series instead of analyzing a time series with itself.…”
Section: Introductionmentioning
confidence: 99%